ROLA I MIEJSCE ADMINISTRACJI SPRAW WEWNĘTRZNYCH W SYSTEMIE WŁADZY PAŃSTWOWEJ II RZECZYPOSPOLITEJ - Andrzej Misiuk (Zeszyty Prawnicze)
ROLE THE INTERNAL AFFAIRS ADMINISTRATION WITHIN THE GOVERNMENT THE IN POLISH SECOND REPUBLIC Summary Basic and primary functions of administration were peacekeeping and regulatory activity. Other, like social, economic and regulatory economic were added in the first half of XIX century. It is safe to say that peacekeeping and regulatory activity were indeed the most important tasks of administrations activity. That was the reason that this predecessor of modern ministry of foreign affairs supervised not only public safety and internal security but also education, relations between state and religion and controlling and audit of other state agendas and local administration. This significant role of ministry of internal affairs remained nearly intact in the Second Republic of Poland. The minister of internal affairs supervised both central administration local administration including controlling over voivodes (centrally-appointed governor of a province in polish voivodeship) and starostas (head of county in polish starostwo).